Regional Participation within European multi-level governance. Saxony-Anhalt: regional parliament, regional government, stakeholders. - Salageanu, Romana (Budrich Unipress, 2017)
Why is there a regional participation of Saxony-Anhalt within the European Multi-Level Governance system? The author provides an account of the characteristics of European Multi-Level Governance (EMLG) and regional participation therein, by describing the EMLG and identifying its topics and categories of meaning for regional participation. She establishes the mechanisms responsible for regional participation, highlighting the patterns that emerge. The features of regional participation are explained based on the examples of the case study Saxony-Anhalt and should inspire other regional actors to pursue their participation within European Multi-Level Governance. The book does not offer the entire picture of EMLG with all decision-making processes involved, but it offers the picture of the regional dimension of this overall phenomenon. The analysed data is based firstly on the literature on the subject of EMLG and regional participation and, secondly on documents from all EU levels (supranational, national and regional). The contribution of this book is providing a constellation of regional participation that can be considered best-practice. This is especially valuable for actors from the new member states of the EU, where regional participation can or still needs to be built up and strengthened.
Keywords: Regionalpolitik; Bundesland; Landespolitik; Landtag; Landesregierung; Politikwissenschaft; Partizipation; Chemieindustrie; Governance; Europäisierung; Regionalisierung; Mehrebenensystem; Akteursforschung; Industriepolitik